Play—An essential part of children’s lives and their computational empowerment - Tikkanen, Ruut; Iivari, Netta; Paananen, Pirkko (Frontiers in Education, 2023)
This article addresses the computational empowerment of children, with an emphasis on the importance of play in realizing it. Although play has been brought up as central for children within numerous disciplines, there is a lack of thorough treatment of the phenomenon in the context of technology design, computational thinking, and computational empowerment. The objective of this research is to open the eyes of adults to see children’s play and improvisation as not only an essential part of children’s life but also an important part of their computational empowerment. We organized numerous participatory design sessions with children (aged 5–6 years), during which play was supported to obtain material for designing a music game. We analyzed the collected data with a framework combining aspects on computational empowerment and play. Our analysis of the sessions showed that play had numerous important functions in the design sessions with the children. Our examination revealed that play is intertwined with computational empowerment in many ways and it supports different aspects of computational empowerment. We recommend that researchers offer various forms of play for children during design sessions to support children’s creativity, narratives, embodiment, and, ultimately, their computational empowerment.